PENGARUH KUALITAS PRODUK, HARGA, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPATU CONVERSE DI SENAYAN CITY - Niken Aprilia; Tukidi (Jurnal Manajemen, 2021)
This study aims to determine the effect of product quality, price, and brand image on purchasing decisions for Converse shoes in Senayan City. This research design is causal quantitative. The population in this study are all consumers who use Converse products and the research sample conducted is 115 respondents, the sampling technique used is Nonprobability Sampling, and compiling the sample based on Accidental Sampling. Methods of data analysis using the instruments used, classical assumption test, and hypothesis testing. The results showed that Product Quality (X1), Price (X2), and Brand Image (X3), both simultaneously and partially had a positive and significant effect on Purchase Decisions.